EAACI/ENDA Position Paper: Diagnosis and management of hypersensitivity reactions to non‐steroidal anti‐inflammatory drugs (NSAIDs) in children and adolescents. Issue 5 (13th June 2018) - Kidon, Mona; Blanca‐Lopez, Natalia; Gomes, Eva; Terreehorst, Ingrid; Tanno, Luciana; Ponvert, Claude; Chin, Chiang Wen; Caubet, Jean Christoph; Soyer, Ozge; Mori, Francesca; Blanca, Miguel; Atanaskovic‐Markovic, Marina
Abstract: Non‐steroidal anti‐inflammatory drugs (NSAIDs) are commonly used in the pediatric population as antipyretics/analgesics and anti‐inflammatory medications. Hypersensitivity (HS) reactions to NSAID in this age group, while similar to adults, have unique diagnostic and management issues. Although slowly accumulating, published data in this age group are still relatively rare and lacking a unifying consensus. This work is a summary of current knowledge and consensus recommendations utilizing both published data and expert opinion from the European Network of Drug Allergy (ENDA) and the Drug Hypersensitivity interest group in the European Academy of Allergy and Clinical Immunology (EAACI). This position paper summarizes diagnostic and management guidelines for children and adolescents with NSAIDs hypersensitivity. Abstract :